Butylated lignin as a compatibilizing agent for polypropylene-based carbon fiber-reinforced plastics. Issue 10 (October 2018) - Sakai, Hiroki; Kuroda, Kosuke; Tsukegi, Takayuki; Ogoshi, Tomoki; Ninomiya, Kazuaki; Takahashi, Kenji
Abstract Lignin is a renewable resource, but it is also considered a waste or a very-low-value material. Herein, we propose a lignin-derived compatibilizing agent as an alternative to the current compatibilizing agents. We prepared a polypropylene-based carbon fiber-reinforced plastic (CFRP) with butylated lignin (C4 lignin). Upon the addition of C4 lignin, the dispersion of carbon fiber into the matrix, and the adhesion between the carbon fiber and the matrix were greatly improved. As a result, the tensile strength of the CFRP prepared with C4 lignin was greater than that of the CFRP without lignan lignin (37.1 compared to 40.2 MPa). This value is close to that of CFRPs prepared with maleic anhydride-modified polypropylene (40.9 MPa), an existing compatibilizing agent. C4 lignin is a promising candidate for biomass-derived compatibilizing agents for polypropylene-based CFRPs. Butylated lignin was applied as a compatibilizing agent of polypropylene-based carbon fiber-reinforced plastics. The butylated lignin increased the tensile strength of the carbon fiber-reinforced plastic from 37.1 to 40.2 MPa, which was similar to what was achieved with a well-known oil-based compatibilizing agent (40.9 MPa).